Avaliação do potencial mitigador da sílica ativa e do metacaulim frente à formação de etringita tardia – DEF em concretos - Oliveira, Solanda de (2022)
Delayed ettringite formation, or DEF, is an internal expansive reaction of hardened concrete that occurs due to the chemical reactions of sulfate ions from Portland cement under high temperatures. The phenomenon begins when, at the first hours of hydration, the temperature enhances levels above 60-65ºC due to the heat of hydration of Portland cement in massive structures with high binder content or in cases of concrete submitted to heat-curing process, being one of the causes of concrete expansion and cracking. Thus, DEF can damage concrete structures over time, impairing its durability and safety. This research presents the use of mineral admixtures, specifically silica fume (SF) and metakaolin (MTC), in different rates as partial replacement of Portland cement (Brazilian Type CP V – high early strength), to mitigate the expansion and damage caused by DEF. The behavior of these pozzolans was evaluated throughout mortars and concrete with and without mineral admixtures. Besides, the DEF occurrence in lab was stepped up by a controlled heat curing process. So, the mechanical and microstructural properties could be assessed to qualify damages in concrete. An overview of degradation caused by DEF, assessed both by the test results and the damage rating index (DRI), could be provided. As a result, the reference mortar (without any mineral admixture) presented, by far, the highest expansions, up to 0.90% at 450 days. In the other hand, the mortars with mineral admixtures presented expansion values less than 0.04% at 450 days. Regarding the expansion of concrete, the reference one (REF) presented expansion of 1% at the age of 365 days. The SA8 concrete (with 8% of silica fume) had expansion around 0.30% and the others - SA12, MCT12 and MTC14 concrete - presented expansion values less than 0.04% at the age of 350 days. The type and content of mineral admixtures led to a great difference in the mixture behavior, with the performance improved by using high contents of metakaolin and silica fume. Nonetheless, it is important to note that the modulus of elasticity decreased about 15% in MTC12 concrete versus 70% of REF concrete. In the case of compressive strength, DEF promoted reductions about 10% for MTC concrete and about 44% for REF concrete. The tensile strength reduced up to 40% for REF and SA8 concrete, while the MTC concrete reached levels far below than that. The deterioration indexes varied from 300 to 700 for the studied concrete of this research, standing greater for REF concrete and for SA8 one. As conclusion, it could be seen that, even though silica fume and metakaolin reduced the damages, they were not able to mitigate entirely DEF, what indicates that they were not enough to contain its occurrence and development over time.